Minipig cytochrome P450 3A, 2A and 2C enzymes have similar properties to human analogs - Soucek, P; Zuber, R; Anzenbacherová, E; Anzenbacher, P; Guengerich, F P (BMC pharmacology, 2001)
BACKGROUND: The search for an optimal experimental model in pharmacology is recently focused on (mini)pigs as they seem not only to be an alternative source of cells and tissues for xenotherapy but also an alternative species for studies on drug metabolism in man due to similarities between (mini) pig and human drug metabolizing systems. The purpose of this work is to characterize minipig liver microsomal cytochromes P450 (CYPs) by comparing their N-terminal sequences with corresponding human orthologs. RESULTS: The microsomal CYPs exhibit similar activities to their human orthologous enzymes (CYP3A4, nifedipine oxidation; 2A6, coumarin 7-hydroxylation; 2D6, bufuralol 1'-hydroxylation; 2E1, p-nitrophenol hydroxylation; and 2C9, tolbutamide hydroxylation). Specific minipig CYP (2A, 2C and 3A) enzymes were partially purified and proteins identified by immunostaining (using antibodies against the respective human CYPs) were used for N-terminal amino acid sequencing. From comparisons, it can be concluded that the sequence of the first 20 amino acids at the N-terminus of minipig CYP2A is highly similar to human CYP2A6 (70% identity). The N-terminal sequence of CYP2C shared about 50% similarity with human 2C9. The results on the minipig liver microsomal CYP3A yielded identical data with those obtained for amino acid sequences of the pig CYP3A29 showing 60% identity with human CYP3A4. CONCLUSIONS: Thus, our results further support the view that minipigs may serve as model animals in pharmacological/toxicological studies with substrates of human CYP enzymes, namely, of the CYP3A and CYP2A forms.
Keywords: Microsomes, Liver; Swine, Miniature; systém (enzymů) cytochromů P-450; steroidhydroxylasy; Aryl Hydrocarbon Hydroxylases; substrátová specifita; Cytochrome P-450 CYP3A; Steroid Hydroxylases; Cytochrome P-450 Enzyme System; miniaturní prasata; zvířata; Humans; Species Specificity; Substrate Specificity; jaterní mikrozomy; druhová specificita; Sequence Analysis, Protein; cytochrom P-450 CYP3A; aromatické hydroxylasy; sekvenční analýza proteinů; lidé; Animals